Serotonin Reuptake Inhibitors in Obstructive Sleep Apnea: Associations in People with and without Epilepsy. (28th August 2018) - Cheng, Jocelyn Y.
Abstract : Purpose . Positive airway pressure remains the gold-standard treatment for OSA, but many are intolerant. The neurotransmitter serotonin is involved in respiratory control. Evidence exists for SRIs in reducing OSA severity in the general population and ictal hypoxemia and seizure-induced respiratory arrest in people with epilepsy (PWE). However, the association between SRIs and OSA severity has not been studied in populations consisting of both groups. This study aims to determine if SRIs are associated with OSA severity in both PWE and people without epilepsy (PWO) and whether differences exist between the two groups. Methods . A retrospective study of adults with OSA was conducted. Subjects were categorized as PWE or PWO and for the use (+SRI) or absence (-SRI) of an SRI. The primary outcome was OSA severity relative to SRI status. OSA severity as a function of SRI status was also compared between PWE and PWO and within the PWE and PWO cohorts. Oxygen saturation nadir was a secondary outcome measure. Statistical adjustment of pertinent characteristics was performed. Results . There were 125 subjects (57 PWE, 68 PWO, 80 –SRI, and 45 +SRI). +SRI was associated with reduced odds of severe compared to moderate OSA, in unadjusted and adjusted analysis. Compared to PWO, PWE demonstrated a more robust association between OSA severity and +SRI. When analyzed as separate cohorts, only PWE demonstrated reduced OSA severity, with adjustment for age (OR:0.140, CI:0.021-1.116, and p=0.042). Oxygen saturation nadir was not significant in any model. Conclusions . SRIs represent a potential treatment option for OSA and may demonstrate a more robust association with reduced OSA severity in PWE compared to PWO.